2017
DOI: 10.18203/issn.2454-5929.ijohns20170946
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological study of masses of nasal cavity paranasal sinuses and nasopharynx

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">A variety of inflammatory, non neoplastic and neoplastic masses involving nasal cavity, paranasal sinuses and nasopharynx are commonly encountered in ENT clinics. The objective was to study the demographic profile, clinical presentation, radiological findings and its correlation with the histopathological findings of masses of nasal cavity, paranasal sinuses and nasopharynx. </span></p><p class="abstract"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…11 The study conducted by Sharma et al also found similar results with male to female ratio of 1.38:1. 12 Another study done by Lathi et al showed similar findings with male to female ratio of 1.5:1. 13 Males are often exposed to dust, infection and smoking habits, and have more outdoor functioning as compared to females.…”
Section: Discussionmentioning
confidence: 57%
“…11 The study conducted by Sharma et al also found similar results with male to female ratio of 1.38:1. 12 Another study done by Lathi et al showed similar findings with male to female ratio of 1.5:1. 13 Males are often exposed to dust, infection and smoking habits, and have more outdoor functioning as compared to females.…”
Section: Discussionmentioning
confidence: 57%
“…1 In a study conducted by Sharma et al the most common observation among the masses of nasal cavity, paranasal sinuses and nasopharynx were nasal polyposis (86%) and the most common presentation was nasal obstruction, nasal discharge & post-nasal discharge. 8…”
Section: Discussionmentioning
confidence: 99%
“…4 Similarly, Sharma et al did not find any case of mycotic infection in their study of 50 cases at Patiala. 5…”
Section: Introductionmentioning
confidence: 99%